Income inequality and financialization: a not so straightforward relationship - Alexiou, Constantinos; Trachana, Emmanouil; Vogiazas, Sofoklis (Emerald, 2021)
Purpose The authors explore the impact of financialization on income inequality for a panel of 19 OECD countries over the period 2000–2017. The authors control for the effect of banking crises, credit market regulation and globalization, among other factors. Design/methodology/approach The authors use three proxies for income inequality and four proxies for financialization. The authors employ a panel fixed effects approach using Driscoll and Kraay’s (1998) nonparametric covariance matrix estimator, which produces standard errors that are robust to general forms of cross-sectional dependence. Findings The authors provide evidence which to a great extent supports the view that the process of financialization has increased income inequality. In the disposable Gini specifications, two out of the four financialization measures are found to significantly contribute to rising inequality whilst in the specification with the market income Gini coefficient, three out of the four financialization proxies appear to adversely affect inequality. In the specification with the Gini coefficient based on manufacturing pay, the evidence is weak. Furthermore, trade unions appear to play a significant role in reducing inequality in two out of the three Gini specifications while the effect of credit market regulation is rather ambiguous. Originality/value The authors’ findings suggest a positive relationship between financialization and income inequality; however, the results depend on the proxies used to measure financialization and income inequality. The authors conclude that the process of financialization in triggering income inequality is complex and merits additional research.
Keywords: Income inequality; Financialization; Credit regulation; Unionization